Individual psychological characteristics of wives whose husbands are alcohol dependent - Aymedov, K. V.; Aseyeyva, Yu. O. (Journal of Education, Health and Sport, 2016)
Aymedov K. V., Aseyeyva Yu. O. Individual psychological characteristics of wives whose husbands are alcohol dependent. Journal of Education, Health and Sport. 2016;6(11):767-774. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.269692 http://ojs.ukw.edu.pl/index.php/johs/article/view/4243 https://pbn.nauka.gov.pl/sedno-webapp/works/792924 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF WIVES WHOSE HUSBANDS ARE ALCOHOL DEPENDENT K. V. Aymedov, Yu. O. Aseyeyva Odessa National Medical University, Ukraine dgylia-as@rambler.ru Abstract Some peculiarities of the humans living together with alcohol-dependent persons have been analyzed. Feminine codependency was clarified and some features of gender “I-conception” were described. Certain types of character accentuation of personality traits were emphasized. It is necessary to develop psychocorrective complexes for codependent women help. Key words: codependency, alcohol dependence, addictive behavior, accentuation of character.